Estimation of the Extraterrestrial Total Solar Irradiance in function of number of sunspots - Plascencia Sánchez, Edisón (2006)
The Total Solar Irradiance (TSI) is the total amount of solar energy  present per square unit every moment beyond the atmosphere, so it's changing every time along the year, although for many practical purposes its average is taken and has been called:  The Solar Constant (1367 W/m2). In this paper, the historical efforts made to quantifcate the TSI are reviewed, the latest advances in this matter are presented and a new method to calculate its monthly average based on the SunSpot Number is proposed to apporach to its value as close as 0.05. W/m2 (RMS = 0.002).